Second cancer in Philadelphia negative myeloproliferative neoplasms (MPN-K). A nested case-control study - Barbui, Tiziano; Ghirardi, Arianna; Masciulli, Arianna; Carobbio, Alessandra; Palandri, Francesca; Vianelli, Nicola; De Stefano, Valerio; Betti, Silvia; Di Veroli, Ambra; Iurlo, Alessandra; Cattaneo, Daniele; Delaini, Federica; et al. (Leukemia, 2019)
We conducted a large international nested case-control study including 1881 patients with Philadelphia-negative myeloproliferative neoplasms (MPN). Cases (n = 647) were patients with second cancer (SC: carcinoma, non-melanoma skin cancer, hematological second cancer, and melanoma) and controls (n = 1234) were patients without SC, matched with cases for sex, age at MPN diagnosis, date of MPN diagnosis, and MPN disease duration. The aim was to evaluate the risk of SC after exposure to cytoreductive drugs. Patients exposed to hydroxyurea (HU) (median: 3 years) had a risk of SC similar to unexposed patients (OR = 1.06, 95% CI 0.82-1.38). In contrast, in cancer-specific stratified multivariable analysis, HU had two-fold higher risk of non-melanoma (NM) skin cancer (OR = 2.28, 95% CI 1.15-4.51). A significantly higher risk of NM-skin cancer was also documented for pipobroman (OR = 3.74, 95% CI 1.00-14.01), ruxolitinib (OR = 3.87, 95% CI 1.18-12.75), and for drug combination (OR = 3.47, 95% CI 1.55-7.75). These three drugs did not show excess risk of carcinoma and hematological second cancer compared with unexposed patients. Exposure to interferon, busulfan, and anagrelide did not increase the risk. In summary, while it is reassuring that no excess of carcinoma was documented, a careful dermatologic active surveillance before and during the course of treatments is recommended.
Keywords: filadelfský chromozom; nitrily; studie případů a kontrol; sekundární malignity; pipobroman; hydroxymočovina; Pyrimidines; protinádorové látky; Philadelphia Chromosome; Pipobroman; Humans; pyrimidiny; Antineoplastic Agents; Thrombocythemia, Essential; polycythaemia vera; pyrazoly; Case-Control Studies; Primary Myelofibrosis; Polycythemia Vera; Hydroxyurea; Nitriles; Pyrazoles; lidé; Neoplasms, Second Primary; esenciální trombocytemie; primární myelofibróza